(3RHOI GdBKGQ ajeG hbY dLGeYg aj GdEbGeI hGdCSaGQ (B/s - (3GHf ScjcQ, eMeO Hf CMeO Hf eMeOs (3Jhaj MhGdj (B1579s; (3GdQhGVjI, GdegOj YjOs; (3GHf ScjcQ, eMeO Hf CMeO,s (3Jhaj MhGdj (B1579.s ((3CHh XHj (B- (3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdShjOj ddfTQ hGdJhRjY ,s (3HjQhJ (B- (3dHfGf (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ ,s (3YeGf (B- (3GdCQOf (B:s (3OGQ GdaGQS ddfTQ hGdJhRjY ,s, 2023)
(3gPg KGdK QMdI hUdfG fUgG dQMGdI YQHj aj GdYgO GdYKeGfj, HYO QMdI HOQ GdOjf GdZRj GdJj bGe HgG aj SfI (B936 (3g` (B/1530 (3e HSHH YRdg ef hXjaI JOQjS cGf jJhdGgG, hQMdI (B((3SaGQI(B) (3bWH GdOjf GdfgQhGdj Gdecj aj SfI (B956 (3g`(B/1558 (3e eQSdG ef WQa CejQ ecIGdTQja MSf Hf CHj fej Edi GdSdWGf SdjeGf GdbGfhfj, ddeWGdHI HYRd hGdj GdeOjfI GdefhQI GdeOYh Odh HjQj hGdPj CXgQ GdESGAI dCTQGa GdMLGR hHGdZ aj GdJWGhd Ydjge, hcGfJ QMdI ScSjcQ HYO YTQ SfhGJ abW ef QMdI GdfgQhGdj, eOahYG HGdgOa PGJg Gdj CdLC HOQ GdOjf GdZRj dJLTe GdSaQ hGdQMdI(B.s
(3GdcJGH GdMGFR Ydi LGFRI GHf HWhWI dCOH GdQMdI aQY JMbjb GdeNWhWGJ (B2022 - 2023.s
(3cTGaGJ (B: (3UaMI (B355-396.s
(3NWhW GdZdGa (B: (3eMeO fLjH HQHhQ ; JUeje GdZdGa (B: (3fGUQ HNjJ ; GdUa GdVhFj (B: (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B339-354.s
Keywords: (3QMdGJ s -- (3JQcjGs -- (3GdTGes